Survivin promotion of melanoma metastasis requires upregulation of α(5) integrin - McKenzie, Jodi A. (Oxford University Press, 2013)
Survivin is an apoptotic and mitotic regulator that is overexpressed in melanoma and a poor prognostic marker in patients with metastatic disease. We recently showed that Survivin enhances melanoma cell motility through Akt-dependent upregulation of α(5) integrin. However, the functional role of Survivin in melanoma metastasis is not clearly understood. We found that overexpression of Survivin in LOX and YUSAC2 human melanoma cells increased colony formation in soft agar, and this effect was abrogated by knockdown of α(5) integrin by RNA interference. We employed melanoma cell xenografts to determine the in vivo effect of Survivin overexpression on melanoma metastasis. Although Survivin overexpression did not affect primary tumor growth of YUSAC2 or LOX subcutaneous tumors, or indices of proliferation or apoptosis, it significantly increased expression of α(5) integrin in the primary tumors and formation of metastatic colonies in the lungs. Additionally, Survivin overexpression resulted in enhanced lung colony formation following intravenous (i.v.) injection of tumor cells in vivo and increased adherence to fibronectin-coated plastic in vitro. Importantly, in vivo inhibition of α(5) integrin via intraperitoneal injection of an α(5)β(1) integrin-blocking antibody significantly slowed tumor growth and reduced Survivin-enhanced pulmonary metastasis. Knockdown of α(5) integrin in cells prior to i.v. injection also blocked Survivin-enhanced lung colony formation. These findings support a direct role for Survivin in melanoma metastasis, which requires α(5) integrin and suggest that inhibitors of α(5) integrin may be useful in combating this process.